Discourses from Latin America and the Caribbean Current Concepts and Challenges - Esposito, Eleonora; Pérez-Arredondo, Carolina; Ferreiro, José Manuel; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2019)
This edited collection brings together the latest research on discourse and society in Latin America and Caribbean in one volume. Employing cross-cutting approaches to current political, institutional and media discourses, it bridges existing theoretical and analytical gaps between the socio-political macro issues and the micro aspects of linguistic analysis to provide fresh insights that deconstruct the complex socio-political power dynamics in Latin America and the Caribbean. Across eight chapters this volume explores the regions' thorny relationship with their complex histories of colonialism and slavery as well as the ongoing, multifaceted constructions of hegemonic and counter-hegemonic identities at the individual, regional and national levels. In doing so, it demonstrates the unique and rich particularities of these regions and why it is that they challenge many conventional dogmas and methods across the Social Sciences. This book will be of particular interest to scholars working in Discourse Studies, Sociology, Politics, Anthropology and Latin American and Caribbean Studies.
Chapter 1. Introduction; Eleonora Esposito, Carolina Pérez-Arredondo, and José Manuel Ferreiro -- Part I Ethnic and Latin American identities construction in intercultural and multinational settings -- Chapter 2. Discursive Re-Foundation of an Intercultural Abya Yala: Morales' Discourse in the Midst of Crisis and the Tradition of Protest; Katharina Friederike Gallant -- Chapter 3. The Discursive Construction of a Latin American Identity/ies in the UN Mission in Haiti (2004-2013); Jose Manuel Ferreiro -- Part II -- Multimodal and Corpus-Assisted approaches to Hegemonic and Resistance discourses in Latin America -- Chapter 4. The hooded student as a metaphor: Multimodal recontextualization of the Chilean student movement in a broadcast news report; Carolina Pérez-Arredondo and Camila Cárdenas-Neira -- Chapter 5. The Zapatista Linguistic Revolution: A Corpus-Assisted Analysis; Isabelle Gribomont -- Part III Discourses of Slavery Reparation and Immigrant Integration from the Caribbean and Latin America -- Chapter 6. The social media campaign for Caribbean Reparations: A critical multimodal investigation; Eleonora Esposito -- Chapter 7. Towards socio-cultural recognition and integration of Latin American immigrants in Los Angeles through the analysis of social-discursive significations; Ricardo Medina Audelo -- Part IV Integrated Approaches to Race and Gender in the Caribbean -- Chapter 8. Remaking Jamaica: tourism, labour and the Awakening Jamaica exhibition; Karen Wilkes -- Chapter 9. Being Said/Seen to Care: Masculine Silences and Emerging Visibilities of Intimate Fatherhood in Dominica, Lesser Antilles; Adom Philogene Heron.
Keywords: Linguistics -- Methodology; Ethnology -- Latin America; Culture; Latin America -- History; Computational linguistics; Philosophy of mind; Self; Research Methods in Language and Linguistics; Latin American Culture; Latin American History; Computational Linguistics; Philosophy of the Self